Dehumanized and demonized refugees, zombies and World War Z. Issue 1 (2nd January 2019) - Crofts, Penny; Vogl, Anthea
ABSTRACT: This paper explores inhuman/human constructions that feature in state responses to refugees. We move beyond straightforward normative claims that dehumanizing or demonizing refugees is unfair, unjust or bad to ask: what kind of inhuman monsters are refugees characterized as when they are 'demonised'; and, what are the consequences of such a characterization? Our argument is that reading the demonised refugee as the contemporary zombie monster and inversely, reading the resurgence of the zombie monster through the prism of the so-called refugee and migrant crisis, reveals the precise anxieties brought about by refugees and asylum seekers. In particular, we claim that both figures represent the transgression of borders, as well as the failure of containment, borders and border walls as a response to crisis. We also argue that the contemporary zombie, as a race-less catchall monster figure, mirrors the erasure of colonial histories, race and race relations in the casting of refugees as dehistoricized, invading and disorderly bodies. We analyse these themes through the 2013 blockbuster film World War Z (dir. Marc Foster). In the film, the United Nations, US Navy, World Health Organisation, and Gerry Lane (a former UN employee) combine to fight a global zombie war.